“Sorting out a Pack of Cards”: Gambling, Card-Playing and Figuring Credit and Social Identity in Georgian England - Vanessa Alayrac-Fielding (Etudes Epistémè)
In the eighteenth century, gambling was the object of many moralising discourses, in essays, plays, newspaper publications and novels, as well as in the visual arts, denouncing the potentially fatal consequences of such an addiction on family fortunes. Gambling also served as a metaphor to describe the new economy’s credit system, leading to the development of a textual and visual rhetoric founded on card-playing imagery. This article explores the use of the image of cards and card games as a trope to discuss the period’s economic transformations and to define social and political identities of public male and female figures, men and women alike. The satirical representations of Charles James Fox and Georgiana Cavendish, two notorious gamblers (and friends), in the shape of playing cards, will be discussed in connection to their gambling addiction and political engagement. Lastly, the image of card-playing will be examined in the dual representation of female gamblers as victims or agents.